Optimization of tuning PID controllers under IAE criteria applied to thermal processes (2015)
Equations tuning for PID controllers integrated approach are widely used in industry. Have developed different types of tuning equationsincluding the most used is the IAE. In the literature several types of tuning equations are reported, but these look satisfactory operation of the control loop but not the optimal operation with a minimum value in the response of the controlled variable. In this research, the response is optimized when IAE equations tuning is used in PID controllers, which seeksto minimize the deviation of the controlled variable to the set point for regulatory control, in order to decrease the value of IAE, which is necessary in critical applications such as the paper industry, where the management of temperature deviation is critical for the final product quality